2023
DOI: 10.1177/21582440231181432
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Flexibility and Organizational Performance: Mediating Role of Innovation

Abstract: Strategic flexibility is deemed to be an important organizational capability for enhancing innovation and improving organizational performance (OP) in uncertain, turbulent, and ever-changing business environments. Many studies have investigated the impact of strategic flexibility on innovation and OP in various contexts and found that strategic flexibility enhances innovation and improves OP. Other studies have found negative association or no association between strategic flexibility and OP. Therefore, it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 85 publications
0
0
0
Order By: Relevance
“…The "Harman's single factor test" estimates two things: 1) emergence of a single factor, and 2) total variance of a single factor. If a single factor does not emerge or total variance of a single factor is higher than 50% then common method bias exists in the collected data (Awais et al, 2023). The results of "Harman's single factor test" in this study indicated that a single factor emerged and total variance of a single is 41.77%.…”
Section: Testing Of Non-response and Common Methods Biasmentioning
confidence: 64%
See 1 more Smart Citation
“…The "Harman's single factor test" estimates two things: 1) emergence of a single factor, and 2) total variance of a single factor. If a single factor does not emerge or total variance of a single factor is higher than 50% then common method bias exists in the collected data (Awais et al, 2023). The results of "Harman's single factor test" in this study indicated that a single factor emerged and total variance of a single is 41.77%.…”
Section: Testing Of Non-response and Common Methods Biasmentioning
confidence: 64%
“…Usually a p-value is tested to see the significance of differences in the early and late responses. If p > 0.05 then there is no significant difference in early and late responses whereas if p < 0.05 then there is a significant difference between early and late responses (Awais et al, 2023). In this study, the researcher applied "Levene's Test for Equality of Variances".…”
Section: Testing Of Non-response and Common Methods Biasmentioning
confidence: 99%